ANISOTROPIC TECHNICAL PROPERTIES OF BUILDING STONES AND THEIR DEVELOPMENT DUE TO FABRIC CHANGES - Strohmeyer D.; Siegesmund S. (My University, 2002)
Technical properties of building stones are of critical importance in applied geosciences such as engineering geology, and also with respect to construction or building physics. Among the many factors which control the technical properties, special importance is given to the rock fabrics influencing the anisotropy of these technical properties. To demonstrate this relationship a sequence of mylonitic rocks. i.e. metagranitoid progressively deformed to mylonite and ultramylonite, was selected. The mineralogical and chemical composition of the protolith and mylonite is nearly identical. All investigated parameters (tensile strength, compressive strength, abrasive strength, magnetic susceptibility and ultrasound wave velocities) are anisotropic and finally controlled by the mineralogical composition and the different fabric elements like microstructural features, the crystallographic and shape preferred orientations and the state of microcracking. The development of the rock fabric with mylonitization, in particular the preferred orientation of mica, seems to be most important for the directional dependence of rock physical properties, at least in mica-rich rocks. However, various sets of microcracks, the degree of grain size reduction, the intensity of the foliation and the compositional layering can significantly modify the results. The interaction of superimposing parameters for different technical properties does not allow any simple cross-correlation.